Study on the structural phase transitions in NaSICON‐type compounds using Ag3Sc2(PO4)3 as a model system. Issue 1 (25th January 2021) - Redhammer, Günther J.; Tippelt, Gerold; Stahl, Quirin; Benisek, Artur; Rettenwander, Daniel
Abstract : The superionic conducting Na Super‐Ionic CONducting‐type (NaSICON‐type) material Ag3 Sc2 (PO4 )3 was studied by single‐crystal X‐ray diffraction between 100 and 520 K. Two phase transitions were found, at 177 and 291 K. Full structural characterization of the three polymorphs is given for the first time. Abstract : NaSICON (Na Super‐Ionic CONducting) structured materials are among the most promising solid electrolytes for Li‐ion batteries and `beyond Li‐ion' batteries ( e.g. Na and K) due to their superior ionic conductivities. Although this material has been well known for decades, its exact phase behaviour is still poorly understood. Herein, a starting material of Na3 Sc2 (PO4 )3 single crystals is used, grown by flux methodology, where Na is subsequently chemically replaced by Ag, in order to take advantage of the higher scattering contrast of Ag. It is found that the NaSICON‐type compound shows two phase transitions from a low‐temperature monoclinic α‐phase to a monoclinic β‐phase at about 180 K and to a rhombohedral γ‐phase at about 290 K. The framework of [Sc2 (PO4 )3 ] 3− is rigid and does not change significantly with temperature and change of symmetry. The main driving force for the phase transitions is related to order–disorder phenomena of the conducting cations. The sensitivity of the phase behaviour on the ordering of these ions suggests that small compositional changes can have a great impact on the phase behaviour and, hence, on the ionic conductivity of NaSICON‐structured materials.